Enhancing The Accounting Skills of Grade 12 Accountancy, Business and Management Learners in Don Eulogio de Guzman Memorial National High School - Narciso A. Martin, Jr.; Dolphy Patacsil; Ricky Retuerne; Donita Gali (Southeast Asian Journal of Science and Technology, 2020)
Abstract – This research used descriptive-survey methodologies to describe the Grade 12 ABM learners' Accounting skills in Don Eulogio de Guzman Memorial National High School. The total sampling was sixty-nine (69) respondents who took the Fundamentals of Accountancy, Business and Management I/II (Service and Merchandising Businesses), which comprised thirty-three (33) learners in Section A and thirty-six (36) learners in Section B. The data collected were analyzed using thematic, frequency count, mean, percentage, and rankings. Data revealed that the problems encountered on the Accounting subjects by the Grade 12 ABM learners were; ranked 1 was Journalizing Entries as confirmed by 51% of the respondents, ranked 2 was Transaction Analysis as confirmed by 22% of the respondents, ranked 3 was Difficult Subjects as confirmed by 17% of the respondents, ranked 4 was Worksheet Preparation as confirmed by 7% of the respondents, and 3% of the respondents confirmed that they did not encounter any problems in taking the Accounting subjects. Among the recommendations of this study were providing more practice drills and problem-solving to increase confidence in Debit and Credit's rules. Accounting teachers should ensure that all learners fully understand the core competencies in the Accounting Cycle before advancing and may incorporate the proposed Strategic Subject Plan (SSP) into the actual teaching process.